2023
DOI: 10.1001/jamanetworkopen.2023.15872
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Equivalence of Biosimilar and Reference Biologic Drugs in Rheumatoid Arthritis

Abstract: ImportanceBiosimilar drugs are potentially lower-cost versions of biologics that may improve access to therapy. However, there is a lack of adequate systematic reviews demonstrating equivalence between these drugs for the treatment of rheumatoid arthritis (RA).ObjectivesTo assess the efficacy, safety, and immunogenicity associated with biosimilars of adalimumab, etanercept, and infliximab compared with their reference biologics in patients with RA.Data SourcesMEDLINE via PubMed, Embase, Cochrane Central Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 100 publications
(1,124 reference statements)
0
9
0
Order By: Relevance
“…As mentioned earlier, the comparative pharmacokinetic, pharmacodynamic, efficacy, safety, and immunogenicity data are stringently reviewed and approved by regulatory agencies [ 12 14 ]. Since the approval of the first biosimilar in 2006, evidence from both clinical studies and real-world experience have validated the comparability between biosimilars and reference products and have shown no significant differences in physiochemical properties and post-translational modifications or impurities [ 12 , 14 , 51 53 ]. Therefore, approved biosimilars can be utilized as a more affordable treatment alternative to their respective reference products [ 12 , 26 , 36 ].…”
Section: Overarching Principles and Consensus Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned earlier, the comparative pharmacokinetic, pharmacodynamic, efficacy, safety, and immunogenicity data are stringently reviewed and approved by regulatory agencies [ 12 14 ]. Since the approval of the first biosimilar in 2006, evidence from both clinical studies and real-world experience have validated the comparability between biosimilars and reference products and have shown no significant differences in physiochemical properties and post-translational modifications or impurities [ 12 , 14 , 51 53 ]. Therefore, approved biosimilars can be utilized as a more affordable treatment alternative to their respective reference products [ 12 , 26 , 36 ].…”
Section: Overarching Principles and Consensus Recommendationsmentioning
confidence: 99%
“…Neutralizing antibodies are typically detected within 6 months of exposure to a biologic agent and can negate drug efficacy. Over the past 17 years since the first approval of a biosimilar, studies have demonstrated no clinically significant differences in the formation of antibodies between biosimilars and reference products [ 14 , 53 , 54 ]. Therefore, antidrug antibodies to biosimilars do not need to be routinely measured in clinical practice [ 12 ].…”
Section: Overarching Principles and Consensus Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As of December 2022, the EMA, FDA, and PMDA had approved more than 90, 40, and 32 biosimilars, respectively. Several studies have shown that biosimilars are equivalent to reference drugs, with varying degrees of price reduction . However, it was reported that biosimilars are still confronted with serious challenges to their use, including patent litigation, exclusivity protection, anticompetitive behavior, and interchangeability requirements, which have limited the use of biosimilars (eTable 1 in Supplement 1).…”
Section: Introductionmentioning
confidence: 99%